(untitled) (Research, Society and Development, 2021)
Temporomandibular disorder is one of the diseases that affect the orofacial region, affecting people’s quality of life, being considered the most complex joint in the entire human body. TMD images can affect approximately 20% of the population asymptomatically or symptomatically. This can cause signs and symptoms such as joint pain and muscle palpation, joint noises, jaw shift, muscle fatigue, headache, tiredness, speech disturbances, earache, spasms, bruxism, and limited jaw function. Currently, this dysfunction is treated by different methods, depending on the need for each case. Despite its notable incidence in the general population, the deficiency of a teaching program in dentistry courses that effectively teaches students is notorious. This work aims to create an information group on TMD, which can serve as a consultative basis for academics and professionals in the field of dentistry. A descriptive narrative review of the literature was carried out, based on scientific articles presented in Portuguese and English, available in databases such as PubMED, Lillacs, BVSsalud and Scielo. The demand for knowledge from professionals increases every day due to the increasing incidence of patients with TMD. It is necessary to have a teaching program within the undergraduate program in Dentistry to train future professionals in the correct diagnosis and treatment of patients with TMDs.